Impact of teacher qualification on students’ achievement in Science (Scholars' Journal, 2020)
This paper analyzed the teachers' qualification and its impact on students’ science achievement in Gorkha district. The purpose of this study was to find out the impact of teacher qualification on student achievement in science teaching and to compare the science achievement of the students taught by trained and untrained teachers. The nature of this study is a mixed-method approach with survey design. To fulfil the objectives of the study, the researchers selected 15 public schools from Gorkha district as a sample, where 5 schools have under Bachelor’s Graduates and 5 schools have Bachelor’s or above graduates but have not teachers’ professional development (TPD) training and 5 schools have Bachelor’s or above graduates having TPD training science teachers. For this study, 15 science teachers and 672 students were selected as a sample by random sampling method. The researchers reviewed the District Level Examination (DLE) result of Gorkha district in the academic year 2016/17. The data was collected from the district education office document of Gorkha district. The primary data were collected through one-week classroom observation and students’ interviews. The study shows that higher qualification teachers, as well as trained teachers, have more techniques and skills of teaching, using methods, materials, evaluation scheme, feedback and other extra activities than the lower qualification and untrained teachers. Also, the result indicates that the science achievement of students taught by trained teachers is greater than the students taught by untrained teachers. Therefore, teacher professional development training and qualification have a positive impact on science learning.